2011
DOI: 10.1039/c0cc03317k
|View full text |Cite
|
Sign up to set email alerts
|

Few constraints limit the design of quinone methide-oligonucleotide self-adducts for directing DNA alkylation

Abstract: Nucleotide sequences minimally containing adenosine, cytosine or guanosine are sufficient to form intrastrand oligonucleotide quinone methide self-adducts reversibly for subsequent alkylation of complementary DNA. The general lack of sequence restrictions should now allow for alkylation of most any target of interest although reaction is most efficient when the self-adducts contain guanine residues and do not form hairpin structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…The rate and final yield of target alkylation can be influenced by the profile of species comprising the self adduct as tested previously by DNA forming hairpin and random coiled structures (13). Early studies on a low molecular weight model QM illustrated a rapid formation of reversible nucleobase adducts through reaction with strong nitrogen nucleophiles such as dG N7, dA N1 and dC N3 that also act as strong leaving groups for QM regeneration (15).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The rate and final yield of target alkylation can be influenced by the profile of species comprising the self adduct as tested previously by DNA forming hairpin and random coiled structures (13). Early studies on a low molecular weight model QM illustrated a rapid formation of reversible nucleobase adducts through reaction with strong nitrogen nucleophiles such as dG N7, dA N1 and dC N3 that also act as strong leaving groups for QM regeneration (15).…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies with DNA-QM conjugates indicated that most any sequence is capable of forming self adducts and transferring its QM to a complementary target (13). Self adducts are likely formed as a heterogeneous mixture of species as a result of QM capture by the various strong nucleophiles present in the attached sequence-directing strand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…QM formation and regeneration are exquisitely sensitive to electronic effects as evident from the five orders of magnitude separating rate constants for QMs differing by a single substituent 31,40 . Although the reversibility of QM reaction may complicate detection of their adducts formed by xenobiotic metabolism of certain drugs and food additives [41][42][43] , the reversibility has allowed for the construction of target-inducible and site-selective alkylating agents [44][45][46] . Prior model studies indicated that the strongest nucleophiles of DNA (G N7, A N1 and C N3) are alkylated by QMs most readily but their resulting adducts dissipate over time as the weakly nucleophilic nitrogens (G N 2 and A N 6 ) and water began to trap the regenerated QM irreversibly 43,47 .…”
mentioning
confidence: 99%
“…guanina u položaju N-1, N-2 ili N-7, adenina u položaju N-6, citozina u N-4 ili timina u položaju N-3 89 . Ovim mehanizmom, primera radi, deluju mitomicin, porfiromicin, karbazilhinon 90 .…”
Section: Interakcije Avarona I Njegovih Derivata Sa Plazmidima Pbr322unclassified